Influence of technological parameters of pressing and ultrasonic fluctuations on adhesional durability of antifrictional polymeric compositions - Дудчак, Т.В.; Дудчак, В.П.; Остапенко, Р.М. (Problems of Tribology, 2014)
The influence of technological parameters of pressing on adhesional durability of polymeric coverings is investigated in the paper. The invesdtigation showed that the adhesional durability is changed in various parameters of pressing from 4 to 18,4 МPа, hardness НВ from 74 to 188 МPа, destroying pressure on compression from 46 to 181 МPа, density from 1544 to 1694 кg/м3. The optimum modes of pressing are determined: the time of endurance under pressure – 0,8 min. / mm, pressure – 54-75 МPа, temperature of pressforms – 438-463 К.